Analisis Kandungan Gizi dan Aktivitas Antioksidan pada Cookies Substitusi Tepung Sorgum (Sorghum bicolor, L) (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Cookies are a practical food, easy to make, and can be stored for a long time. The main raw material for making cookies is wheat flour. Considering that the nutritional content of sorghum is not inferior to wheat flour, sorghum has the opportunity to replace wheat in food processing. The purpose of this study was to analyze the nutritional content and antioxidant activity of cookies substituted with sorghum flour. The design used an experimental study using the RAL (Completely Randomized Design) method. Cookies formulation carried out as many as 4 formulas.The best cookies were analyzed descriptively with the mean value and one-way-anova. The nutritional content of cookies was analyzed by gravimetric and titrimetric methods and the antioxidant activity test was analyzed by the DPPH method. The nutritional content of cookies substituted with sorghum flour obtained was the value of carbohydrates (49.9%), protein (5.69%), and fat (25.2%) and the antioxidant activity value of cookies substituted with sorghum flour was 104.48 ppm. The nutritional content of cookies has met the quality requirements of cookies based on SNI. 2793-2011 and the value of antioxidant activity on cookies substituted with sorghum flour is in the medium category based on the IC50 value.